Interaction of genotype and environment: effect of strain and housing conditions on cognitive behavior in rodent models of schizophrenia - Turner, Karly M.; Burne, Thomas H. (Frontiers in Behavioral Neuroscience, 2013)
Schizophrenia is associated with many genetic and environmental risk factors and there is growing evidence that the interactions between genetic and environmental ‘hits’ are critical for disease onset. Animal models of schizophrenia have traditionally used specific strain and housing conditions to test potential risk factors. As the field moves towards testing gene (G) x environment (E) interactions the impact of these choices should be considered. Given the surge of research focused on cognitive deficits, we have examined studies of cognition in rodents from the perspective of GxE interactions, in which strain or housing manipulations have been varied. Behaviour is clearly altered by these factors, yet few animal models of schizophrenia have investigated cognitive deficits using different strain and housing conditions. It is important to recognise the large variation in behaviour observed when using different strain and housing combinations because GxE interactions may mask or exacerbate cognitive outcomes. Further consideration will improve our understanding of GxE interactions and the underlying neurobiology of cognitive impairments in neuropsychiatric disorders.